2015
DOI: 10.1063/1.4916278
|View full text |Cite|
|
Sign up to set email alerts
|

Site-specific probing of charge transfer dynamics in organic photovoltaics

Abstract: We report the site-specific probing of charge-transfer dynamics in a prototype system for organic photovoltaics (OPV) by picosecond time-resolved X-ray photoelectron spectroscopy. A layered system consisting of approximately two monolayers of C60 deposited on top of a thin film of CopperPhthalocyanine (CuPC) is excited by an optical pump pulse and the induced electronic dynamics are probed with 590 eV X-ray pulses. Charge transfer from the electron donor (CuPC) to the acceptor (C60) and subsequent charge carri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(33 citation statements)
references
References 31 publications
4
28
1
Order By: Relevance
“…Photoemission techniques allow to directly ionize core electrons instead of observing core-to-valence transitions, and the method has the additional benefit of exclusively tracing the dynamics of charge state changes and interfacial charge transfer [72,73]. Photoemission techniques in the XUV and x-ray are capable of measuring femtosecond to nanosecond dynamics [74][75][76]. Apart from core-level photoelectron studies, x-rays can be tremendously useful for valence-state photoemission.…”
Section: X-ray Techniques For Following Chemical Dynamicsmentioning
confidence: 99%
“…Photoemission techniques allow to directly ionize core electrons instead of observing core-to-valence transitions, and the method has the additional benefit of exclusively tracing the dynamics of charge state changes and interfacial charge transfer [72,73]. Photoemission techniques in the XUV and x-ray are capable of measuring femtosecond to nanosecond dynamics [74][75][76]. Apart from core-level photoelectron studies, x-rays can be tremendously useful for valence-state photoemission.…”
Section: X-ray Techniques For Following Chemical Dynamicsmentioning
confidence: 99%
“…[126][127][128][129] While its extension to solutions has been achieved for some years now 122,[129][130][131][132][133] it has mostly been used for studies of ET (or electron injection) of sensitized systems, for which they are actually an ideal tool. [134][135][136][137] (B) Deep-ultraviolet spectroscopy Amino-acid residues in proteins and the nucleobases of DNA and RNA all have their absorption bands below 300 nm in the deep-ultraviolet (deep-UV) region. In addition, most large band-gap semi-conductors, such as TMOs or transition metal nitrides, that are of great importance in photovoltaics and photocatalysis, have their band gaps lying below 380 nm, some actually closer to 300 nm.…”
Section: (A) X-ray Spectroscopymentioning
confidence: 99%
“…Recently, time-resolved XPS core-level photoemission measurements performed on donor/acceptor blends of TMC organic molecules and fullerenes [53,54] have shown that the core levels experience binding energy shifts after the systems are excited by a femtosecond optical pump.…”
Section: Thick Films (Intermolecular Interactions Perturb the Dynamics)mentioning
confidence: 99%